Tantangan dan Strategi Audit Internal Menghadapi Era New Normal pada saat Pandemi Covid 19 di Akademi Maritim Nusantara - Hari Sucahyowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2021)
Internal audit has an important role as a line of defense in effective risk management and control inside and outside the organization. The development of the world of education, especially higher education, requires every university to always adapt its business processes. The Covid 19 pandemic was felt not only in Indonesia but also around the world and was a new experience, and suddenly because it was never expected that this situation would occur, so that all organizations adjust their business processes suddenly and without planning. The Covid 19 pandemic must be addressed as soon as possible. The Covid-19 pandemic has affected most of the business processes carried out by QMR (Quality Management Representative) in conducting Internal Audit in universities, so it is necessary to adjust the strategy in carrying out Internal Audit activities.